PENGARUH PEMBERIAN BUKU SAKU TERHADAP TINGKAT PENGETAHUAN SAFETY RIDING : STUDI KASUS DI SMK MUHAMMADIYAH 3 YOGYAKARTA - Lestari, Desy Anif; Arianto, Machfudz Eko (Universitas Ahmad Dahlan, 2020)
Driving safety knowledge is the initial provision that must be possessed before driving on the highway. The purpose of this study was to determine the effect of the provision of safety riding pocketbooks on increasing student knowledge. The research design used in this study was pre-experimental, with one group pretest-posttest design. The sampling technique used was the total population with a large sample of 76 vocational students. The data obtained were analyzed using the Wilcoxon alternative test. Before given the safety riding pocketbook of the 20 most questions with the correct answer that is question number 17 as many as 73 respondents (90.6%), while after being given the safety riding pocketbook of the 20 most questions with the correct answer that is question number 18 as many 76 respondents (100%). The average pretest score is 14.75, while the posttest average value is 17.24, and there is a difference in the average deviation of 2.66 with a p-value of 0,000. It can be concluded that it is statistically significant, and there is an increase in student knowledge after being given a pocketbook. There is a difference in the average safety riding knowledge before. After being given a pocketbook to students of class X and XI majoring in TBSM (Motorcycle Engineering and Business) Vocational school Muhammadiyah 3, Yogyakarta with the p-value is 0,000.